The Saga of the Jómsvikings : A Translation with Full Introduction - Jóhannesdóttir, Þórdís Edda, 1984-; Finlay, Alison (Book collections on Project MUSE., 2018)
Unique among the Icelandic sagas, part-history, part-fiction, the Saga of the Jomsvikings tells of a legendary band of vikings, originally Danish, who established an island fortress of the Baltic coast, launched and ultimately lost their heroic attack on the pagan ruler of Norway in the late tenth century. The saga's account of their stringent warrior code, fatalistic adherence to their own reckless vows and declarations of extreme courage as they face execution articulates a remarkable account of what it meant to be a viking. This translation presents the longest and earliest text of the saga, never before published in English, with a full literary and historical introduction to this remarkable work.